2018
DOI: 10.1007/s12046-018-0914-y
|View full text |Cite
|
Sign up to set email alerts
|

Dye sensitized solar cell efficiency improvement using TiO2/nanodiamond nano composite

Abstract: This paper aims to demonstrate the efficiency and recombination improvement of Dye-sensitized solar cells (DSSCs) by introducing of a Nanodiamond (NDs)-TiO 2 nano composite. The main challenge in the proposed application is to find the optimal wt.% of ND in TiO 2. The experimental tests were conducted to compare the developed NDs/TiO 2 cell with one of pure TiO 2 nanoparticles prepared in the same conditions. It was observed that short circuit current density, power conversion efficiency, fill factor and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[14,15] Properties such as high thermal conductivity, nontoxicity and biocompatibility, high optical transparency, high surface area, and easy surface tunability [16][17][18] make NDs suitable for a wide range of applications including biomedicine, [19,20] water cleaning processes, [21,22] energy storage devices, [23][24][25][26] thin-film electronics, [27,28] and even photovoltaic devices. [29,30] A thorough study of the mechanism of charge transfer to and between nanodiamonds in sensors, energy harvesting, and other applications has been a subject to a number of prior experimental and theoretical studies, which indicated that nanodiamonds can act both as electron donors and acceptors, as well as charge separation interface, including suitable energetic levels. [17,31] In the present work, we investigate the use of such effects in real complete OSC devices.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14,15] Properties such as high thermal conductivity, nontoxicity and biocompatibility, high optical transparency, high surface area, and easy surface tunability [16][17][18] make NDs suitable for a wide range of applications including biomedicine, [19,20] water cleaning processes, [21,22] energy storage devices, [23][24][25][26] thin-film electronics, [27,28] and even photovoltaic devices. [29,30] A thorough study of the mechanism of charge transfer to and between nanodiamonds in sensors, energy harvesting, and other applications has been a subject to a number of prior experimental and theoretical studies, which indicated that nanodiamonds can act both as electron donors and acceptors, as well as charge separation interface, including suitable energetic levels. [17,31] In the present work, we investigate the use of such effects in real complete OSC devices.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies with OSCs attempted to use NDs rather simply based on current knowledge of NDs physics and surface chemistry, focusing mostly on the resulting photovoltaic performance. [29,30,[32][33][34][35][36][37] The NDs made by the detonation method were used in those works. Such NDs exhibit highly defective structures, high sp 2 -C content, and nitrogen impurities due to the use of trinitrotoluene as an explosive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation